An exploration on e-retailers' home delivery – strategic elements and their prioritisation. Issue 3 (6th June 2016) - Wang, Chengbo; Mao, Zhaofang; O'Kane, James; Wang, Jun
Abstract : Purpose: – The purpose of this paper is to introduce a research exploring the important strategic elements and their prioritisation for e-retailers' home delivery logistics process efficacy improvement. Design/methodology/approach: – The research was completed through focus group, survey and importance-performance analysis. Findings: – The research identified, confirmed and prioritised a set of explicitly important strategic elements currently deemed important by e-retailers for ensuring the efficacy of their home delivery logistics process in Chinese marketplace, and also referential to the other similar emerging marketplaces. Research limitations/implications: – The research contributes positively to the enrichment of the theoretical knowledge pool of e-retailers' logistics performance improvement. Practical implications: – The research findings guide/inform the strategy development and implementation for e-retailers entering and/or operating in Chinese marketplace. And the findings can also be referential to the e-retail strategy development for entering and operating in other emerging markets similar to China's. This point is particularly meaningful for those e-retailers that want to expand the outreaching and increase the popularity of their businesses in the global marketplace. Originality/value: – Corresponding to the much needed further research on e-retailing home delivery performance improvement, the research provides findings that add substantial new insights into the field, with a particular focus on China, as one of the emerging developing marketplaces.